2020
DOI: 10.3390/genes11060684
|View full text |Cite
|
Sign up to set email alerts
|

DNA Hypermethylation and Unstable Repeat Diseases: A Paradigm of Transcriptional Silencing to Decipher the Basis of Pathogenic Mechanisms

Abstract: Unstable repeat disorders comprise a variable group of incurable human neurological and neuromuscular diseases caused by an increase in the copy number of tandem repeats located in various regions of their resident genes. It has become clear that dense DNA methylation in hyperexpanded non-coding repeats induces transcriptional silencing and, subsequently, insufficient protein synthesis. However, the ramifications of this paradigm reveal a far more profound role in disease pathogenesis. This review will summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 101 publications
3
11
0
1
Order By: Relevance
“…These results further demonstrate that for DNA and RNA oligonucleotides containing the same number of protonated Cyt base pairs, 5-methylation would tend to stabilize the DNA i -motif conformations more than the RNA counterparts. As 5-hypermethylation of DNA can be severe in diseased states associated with d­(CCG) n ·d­(CGG) n trinucleotide sequences, which are implicated as the cause of Fragile X syndrome among human populations, these findings suggest that the DNA i -motif may play a role . This extrapolation of our results is based on parallel studies conducted in solution that probed a series of unmodified oligonucleotides containing Cyd and their 5-methylated analogues and reported a change in the melting temperature, T m , from 67.7 ± 0.5 to 75.9 ± 0.3 °C, respectively, unambiguously suggesting that duplexes containing 5-methylated Cyt residues are thermally more stable .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These results further demonstrate that for DNA and RNA oligonucleotides containing the same number of protonated Cyt base pairs, 5-methylation would tend to stabilize the DNA i -motif conformations more than the RNA counterparts. As 5-hypermethylation of DNA can be severe in diseased states associated with d­(CCG) n ·d­(CGG) n trinucleotide sequences, which are implicated as the cause of Fragile X syndrome among human populations, these findings suggest that the DNA i -motif may play a role . This extrapolation of our results is based on parallel studies conducted in solution that probed a series of unmodified oligonucleotides containing Cyd and their 5-methylated analogues and reported a change in the melting temperature, T m , from 67.7 ± 0.5 to 75.9 ± 0.3 °C, respectively, unambiguously suggesting that duplexes containing 5-methylated Cyt residues are thermally more stable .…”
Section: Discussionsupporting
confidence: 62%
“…Our results corroborate with previous solution-phase reports that show that DNA forms more stable i-motif conformations than their RNA counterparts. 84,85 Thus, in a previous study aimed at examining the potential of i-motif formation by an 18-mer DNA with its corresponding 18-mer RNA sequence, melting temperatures of 54 and 25 °C, respectively, were reported, indicating a more stable DNA than RNA i-motif structure. 84 Likewise, at a strand concentration of 9.8 mM, melting temperatures of 12 and 69 °C were reported for the RNA [r(UC 5 )] 4 and DNA [r(TC 5 )] 4 i-motif conformations, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…ARX encodes a homeotic bi-functional TF capable of activating or repressing gene transcription [ 15 ]. Mutations in ARX have been found in a wide range of NDDs, affecting only male children and including severe cortical malformations such as X-linked Lissencephaly with agenesis of the corpus callosum and ambiguous genitalia (XLAG; MIM:300215); Agenesis of Corpus Callosum (ACC; MIM 300004; also known as Proud syndrome); severe pediatric epilepsy such as Developmental and Epileptic Encephalopathy 1 (DEE1; MIM:308350, also known as West syndrome); and mild cognition diseases including Partington syndrome (MIM 309510), autism, and non-syndromic intellectual disability [ 4 , 16 , 17 , 18 , 19 , 20 ]. Previous studies conducted by us and other groups have shown that XLAG mutations abrogate the transcriptional program controlled by ARX, whereas expansions of the polyA-tracts are hypomorphic mutations with reduced transcriptional activity and binding properties [ 4 , 5 , 15 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a few examples of larger genomic variants disrupting these near-cis sequences in the context of NDDs. Undoubtedly one of the most well-known examples is the CGG repeat expansion in the 5' UTR of the FMR1 gene, resulting in DNA hypermethylation at the promoter, silencing FMR1 and giving rise to fragile X syndrome 90 . Interestingly, this repeat expansion also disrupts the TAD boundary adjacent to FMR1, decoupling FMR1 from putative downstream enhancers 91 .…”
Section: Disruption Of Near Cis-regulatory Elements (Promoter 5' and 3mentioning
confidence: 99%
“…A GGC repeat expansion in the XYLT1 promoter of patients with Baratela-Scott syndrome results in hypermethylation of the first exon and reduced XYLT1 expression 92 . Repeat expansions also give rise to other forms of ID, including FRAXE (5' UTR of AFF2), FRA2A (promoter of AFF3), and FRA12A (5' UTR of DIP2B) 90 .…”
Section: Disruption Of Near Cis-regulatory Elements (Promoter 5' and 3mentioning
confidence: 99%